2010
DOI: 10.1128/aem.01095-10
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Abundance of Zoonotic Pathogens and Indicators in Manures of Feedlot Cattle in Australia

Abstract: The occurrence of 10 pathogens and three fecal indicators was assessed by quantitative PCR in manures of Australian feedlot cattle. Most samples tested positive for one or more pathogens. For the dominant pathogens Campylobacter jejuni, Listeria monocytogenes, Giardia spp., Cryptosporidium spp., and eaeA-positive Escherichia coli, 102 to 107 genome copies g−1 (dry weight) manure were recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 28 publications
5
27
1
Order By: Relevance
“…In feedlot cattle manures, L. monocytogenes was found to be one of the most predominant pathogens with 10 2 to 10 7 genome copies per gram (dry weight) of manure recovered as assessed by quantitative PCR (Klein et al, 2010).…”
Section: Survival Of Listeria Monocytogenes In Manurementioning
confidence: 99%
“…In feedlot cattle manures, L. monocytogenes was found to be one of the most predominant pathogens with 10 2 to 10 7 genome copies per gram (dry weight) of manure recovered as assessed by quantitative PCR (Klein et al, 2010).…”
Section: Survival Of Listeria Monocytogenes In Manurementioning
confidence: 99%
“…11,12 One interesting fact among bioaerosol studies is that, despite the excretion of zoonotic pathogens by livestock, very few if any are detected downwind of manure application sites and housing units. 13−15 A number of factors could be at play here, as pathogen levels in manures tend to be lower than that of indicator organisms; 16 plus the aerosol sampling methods and ambient conditions (e.g., temperature, humidity, solar radiation) could be impacting the viability of microorganisms resulting in fewer detects if culture-dependent techniques are used for enumeration. While molecular-based methods such as quantitative PCR (qPCR) have increased sensitivity over traditional culture techniques, they cannot distinguish between inactive and infectious organisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Estimation of the risk represented by pathogens in animal manures, however, has largely been based on the cultivation and enumeration of fecal indicator organisms (2, 10). It has been recently shown that molecular methods can be successfully applied with such difficult-to-analyze materials to complement culture-dependent approaches (26,27).In this study, we attempted to use quantitative real-time PCR (qPCR) to enumerate fecal indicator organisms and putative zoonotic pathogens in wastewaters from dairies in southern Idaho. qPCR is often used as a convenient alternative to culture-dependent techniques that has the added advantage of being able to detect viable but nonculturable (VBNC) cells of potential pathogens (7, 27, 59).…”
mentioning
confidence: 99%
“…While numerous studies have measured the occurrence of these zoonotic pathogens in cattle manures and assessed their fate and transport in the environment (41,48,55), to our knowledge, no comprehensive studies have been conducted to quantify pathogens in dairy wastewaters. In addition, only a few studies to date have quantified a wide range of pathogens within cattle manures (20,21,26). Understanding the number of pathogens in any land-applied waste is particularly important when developing a quantitative microbial risk assessment (12,17,56).…”
mentioning
confidence: 99%
See 1 more Smart Citation